Intraoperative Neuromonitoring for Cerebral Arteriovenous Malformations Embolization: A Propensity-Score Matched Retrospective Database Study. (16th November 2020) - Feng, Austin Y; Sussman, Eric S; Jin, Michael C; Wong, Sandy; Lopez, Jaime; Pulli, Benjamin; Heit, Jeremy; Telischak, Nicholas
Abstract: INTRODUCTION: Treatment of cerebral arteriovenous malformations (AVMs) may result in neurologic morbidity, particularly when an AVM is located in or adjacent to eloquent brain regions. Intraoperative neurophysiologic monitoring (IONM) may be utilized to reduce the risk of iatrogenic injury during AVM treatment. METHODS: Admissions for AVM embolization were assessed from the Truven MarketScan Database and Medicare Supplement. Inclusion criteria included continuous enrollment 6-months before and after the index encounter. Use of IONM and presence of intracranial hemorrhage (ICH) were noted. Propensity-score matched cohorts with and without IONM were generated to minimize bias between treatment groups (adjusting for age, sex, and comorbidities). RESULTS: From 2007 to 2016, there were 16, 279 patients diagnosed with cerebral AVM in the MarketScan database, of which approximately 13% underwent endovascular embolization. These embolized patients were stratified into IONM and non-IONM cohorts; in total, there were 357 patients in the IONM cohort and 1, 775 patients in the non-IONM cohort. Provider types were significantly different between cohorts, with neurologists more likely in the IONM group, and radiologists more common in the non-IONM group ( P < . 005). Unruptured AVMs were significantly more likely to be embolized with adjunctive IONM (17.7%) compared to ruptured AVMs (7.9%) ( P < . 005). After balancing for baseline comorbidities, there were 220 patients in the IONM cohort, and 1393 patients in the non-IONM cohort. Amongst unruptured AVM patients, IONM was linked to a significantly shorter length of stay (2.72 versus 4.92 days; P < . 005), significantly lower rates of complications within 30 days of discharge (0.00% versus 1.88%; P = . 038), and a numerically lower 30-day readmission rate that trended towards significance (6.97% versus 10.91%; P = . 133). There was no difference in discharge status between the IONM and non-IONM cohorts. CONCLUSION: Endovascular embolization for unruptured AVMs performed with adjunctive IONM was associated with shorter length of stay and lower complication rates. Additional prospective evaluation of IONM in AVM embolization is warranted.